HYPOVIRULENT ISOLATES OF FUSARIUM COLLECTED FROM CHILI CROPS IN BOYOLALI REGENCY, CENTRAL JAVA, INDONESIA - Supyani Supyani; Sri Widadi (AGRIVITA, Journal of Agricultural Science, 2015)
Fusarium, a genus of filamentous fungi, has many species which serving as important pathogens to many diseases in crops. Till today, there have not been effective and efficient control methods for such fungi. Recently, scientists agree that application of biological agents is a tactful choice. Development of hypovirulent strains of fungus as biocontrol agents is very limited. This research was aimed to find hypovirulent isolates of Fusarium from field as biological agents. A hundred isolates of Fusarium from chili were collected in Boyolali, Central Java. Morphological characterization revealed that isolates performed varied colony phenotypes. Based on colony phenotype pattern, isolates were classified into five groups. From each group, one hypovirulent isolate was selected based on colony growth rate on potato dextrose agar media. The selected hypovirulent isolates were used for virulence assay in apple. The result showed that there were four hypovirulent isolates i.e.: B6, C15, D19, and E20 isolates. Total RNA extraction of the identified hypovirulent isolates revealed the existence of viral RNA in C15 isolate. Based on the existence of viral RNA in C15 isolate, the hypovirulent traits were due to mycoviral infection, whereas the hypovirulent traits performed by the other three were due to genetic factors.